The Effect of Teacher Communication Through Storytelling Method on the Creativity Level of Kindergarten Students in Bekasi City - Afrina Sari; Hermansyah Hermansyah (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
Background - Children's creativity can be increased through learning methods. Creativity in kindergarten student learning aims to develop students' curiosity and develop their imagination. It is suspected that teacher communication in telling a story using the storytelling method will help increase student creativity in Kindergarten in the city of Bekasi. Purpose – This study aims to: 1) analyze the effect of teacher communication variables on the creativity level of kindergarten students in Bekasi City. 2) analyze the storytelling method variable as a mediator variable between teacher communication and students' creativity level. Design/methodology/approach – The research method uses the quantitative-correlation method, namely calculating the relationship between variables using the SPSS application and the Sobel calculator to calculate the mediator variable, whether it can be used as a mediator variable after being calculated by using a Sobel calculator. The population of this study was kindergarten students in Bekasi City who were taken randomly. The research sample was determined in kindergarten schools using the storytelling method as a learning method. Randomly selected, namely private kindergarten